Breaking the waves: Routines and rituals in entrepreneurship education. Issue 2 (April 2017) - Neergaard, Helle; Christensen, Dorthe Refslund
Learning is related to the environment created for the learning experience. This environment is often highly routinized and involves a certain social structure, but in entrepreneurship education, such routinization and structure may actually counteract the learning goals. This article investigates how classroom routines and rituals impact on entrepreneurship education in order to problematize how existing classroom environments may hinder critical learning experiences from taking place. This article builds on extensive insights from six cohorts of students at two Scandinavian universities over a 4-year period (2012–2015). The data were procured using an experiential–explorative research approach in which the researchers were personally involved in reflective processes as co-learners. The findings illustrate how educators can use rituals actively to change how students learn. However, students are very wary of embracing new structures and rituals; indeed, some feel so comfortable with the old rituals that they would prefer not to change from being receivers of knowledge to co-creators of the learning situation. It is therefore important to exchange existing rituals with new ones that enhance the feeling of safety and involve the students in creating the change. This is achieved through scaffolding and setting up ritual markers, which are continuously repeated.